Membrane homeoviscous adaptation in the piezo-hyperthermophilic archaeon Thermococcus barophilus - Cario, Anaïs; Grossi, Vincent; Schaeffer, Philippe; Oger, Philippe M. (Frontiers in Microbiology, 2015)
The archaeon Thermococcus barophilus, one of the most extreme members of hyperthermophilic piezophiles known thus far, is able to grow at temperatures up to 103°C and pressures up to 80MPa. We analyzed the membrane lipids of T. barophilus by HPLC-MS as a function of pressure and temperature. In contrast to previous reports, we show that under optimal growth conditions (40 MPa, 85°C) the membrane spanning tetraether lipid GDGT-0 (sometimes called caldarchaeol) is a major membrane lipid of T. barophilus together with archaeol. Increasing pressure and decreasing temperature lead to an increase of the proportion of archaeol and, reversely, a higher proportion of GDGT-0 is observed under low pressure and high temperature conditions. Noticeably, pressure and temperature fluctuations also impact the level of unsaturation of non-polar lipids with an irregular polyisoprenoid carbon skeleton (polyunsaturated lycopane derivatives), suggesting a structural role for these neutral lipids in the membrane of T. barophilus. Whether these apolar lipids insert in the membrane or not remains to be addressed. However, our results raise questions about the structure of the membrane in this archaeon and other archaeon harboring a mixture of di- and tetraether lipids.